2021
DOI: 10.1136/bmjopen-2020-043976
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of symptoms, time to presentation and barriers to medical help-seeking among Omani women diagnosed with breast cancer: a cross-sectional study

Abstract: ObjectiveTo identify knowledge of breast cancer (BC) symptoms, time taken to consult a doctor and factors contributing to delays in medical help-seeking.DesignA cross-sectional study of Omani women diagnosed with BC.SettingThe two main teaching hospitals in Oman: Royal Hospital and Sultan Qaboos University Hospital.ParticipantsAdult Omani women recently diagnosed with BC.ToolsThe Breast Module of the Cancer Awareness Measure and the International Cancer Benchmarking Partnership questionnaire were used to colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…To our knowledge, this is the first interventional study conducted in Oman to evaluate the effectiveness of a cancer education program in enhancing awareness of BC risk factors and symptoms and reducing barriers to seeking medical help among female Omani adolescent students. In Oman, BC has been ranked as the most commonly diagnosed cancer, with affected women being diagnosed at a younger age and presenting at relatively advanced stages (i.e., stages III or IV) at the time of diagnosis [ 17 , 18 ]. Awareness of evidence-based cancer risk factors has been considered an important component of cancer control strategies [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first interventional study conducted in Oman to evaluate the effectiveness of a cancer education program in enhancing awareness of BC risk factors and symptoms and reducing barriers to seeking medical help among female Omani adolescent students. In Oman, BC has been ranked as the most commonly diagnosed cancer, with affected women being diagnosed at a younger age and presenting at relatively advanced stages (i.e., stages III or IV) at the time of diagnosis [ 17 , 18 ]. Awareness of evidence-based cancer risk factors has been considered an important component of cancer control strategies [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that young Omani women have inadequate knowledge of BC symptoms [ 18 , 19 ]; moreover, such women do not prioritize seeking medical help and report several physical and emotional barriers to help-seeking despite awareness of the importance of an early BC diagnosis [ 18 , 20 , 21 ]. As such, researchers have concluded that there is an urgent need for cancer education programs to be included in local school curricula targeting female adolescents to improve their knowledge of BC symptoms and address help-seeking barriers to minimize delays in BC diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of BC screening practices was attributed to the lack of a doctor’s recommendation, fear, and embarrassment. 33 - 35 El Hajj and Hamid 36 in 2013 pointed out that 88% of pharmacies in Qatar fail to provide education programs for BC, though 60% were eager to participate in the promotion for BC awareness.…”
mentioning
confidence: 99%
“…Relating their 'affective attitude', women in this study mostly felt positive about the INCLUSION approach, but had concerns about its emotional implications in stimulating anxiety or fear which could impede their acceptance and use of new cancer information. Previous studies have also shown fear of diagnosis as a barrier to early presentation for suspected cancer symptoms (Al-Aziz et al, 2021;Macleod et al, 2009) or screening uptake (Bamidele et al, 2017), which highlights the importance of providing cancer information in a clear and reassuring way, to avoid women confusing it with an impending diagnosis.…”
Section: Discussionmentioning
confidence: 99%